Sequence therapy in metastatic pancreatic cancer - Waidmann, Oliver; Pelzer, Uwe; Boeck, Stefan; Waldschmidt, Dirk-Thomas (Zeitschrift für Gastroenterologie, 2018)
Pancreatic cancer is one of the most lethal cancer diseases. For years, gemcitabine has been the standard of care and the only therapeutic option in patients with metastatic pancreatic cancer. Within the last years, new combination therapies have been established for first-line treatment, which significantly improve overall survival in comparison to gemcitabine monotherapy. Furthermore, new second-line therapies have been identified, which significantly improve overall survival. The current manuscript summarizes briefly standard of care first- and second-line chemotherapies and discusses possible treatment sequences.
Keywords: pancreatic cancer; systemic chemotherapy; chemotherapy; sequence therapy; metastatic pancreatic cancer; gemcitabine